Prinsip Kesantunan Berbahasa Siswa Kelas XI SMAN 1 Pekanbaru - Ikhwana, Anisa Nur; Ningsih, Maharani Arya (STKIP PGRI Ponorogo Press, 2024)
This study aims to determine, describe, analyze, and interpret data regarding the politeness principles of class XI SMAN 1 Pekanbaru. This study tries to identify how these students apply several aspects of politeness in their conversations in the school environment. This study focuses on six aspects of politeness principles that are appropriate in the question, namely: politeness maxims of wisdom, politeness generosity maxims, politeness appreciation maxims, politeness modesty maxims, politeness consensus maxims, politeness maxims of sympathy. In this study, the theory used is the theory put forward by Leech, combined with theories from other sources. The research data was obtained through observation of the entire speech of class XI students at SMAN 1 Pekanbaru. The method used in this research is descriptive method with a qualitative approach. Data collection techniques used include observation, recording, and recording.